Bahasa dan Komunikasi dalam Dunia Jurnalistik : Menyampaikan Informasi Akurat - Azhar Dhiya Nahar; Rizki Khisban (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This article examines the role of language and communication in journalism, with a focus on conveying accurate information. In an era where information is disseminated rapidly and in a variety of ways, journalists need to not only report the news but also ensure that the news is credible. This article contributes to a deeper understanding of the relationship between language, communication, and news accuracy by analyzing effective communication methods and the challenges journalists face in maintaining accuracy. The aim is to: This study shows that the use of appropriate language and good communication techniques can increase the credibility of the media.